Tinidazol antibiotic degradation in aqueous solution by zero valent iron nanoparticles and hydrogen peroxide in the presence of ultrasound radiation - Rahmani, H.; Gholami, M.; Mahvi, A.H.; Ali-Mohammadi, M.; Rahmani, K. (Химия и технология воды, 2014)
The purpose of this study was to investigate the efficiency removal of the antibiotic Tinidazol by hybrid system of ultrasonic/nZVI/H₂O₂ (US/nZVI/H₂O₂) in aquatic environment. It examined the effect of variables such as concentration of antibiotic, nZVI and H₂O₂, frequency of US and pH. Also the performance of system in removal of COD and electrical energy consumed by the ultrasonic bath was investigated. Findings showed the best efficiency (93 %) for system in pH 3, concentration hydrogen peroxide of 1M, amount of 0,2 g of zero valent iron nanoparticles and 130 kHz radiation frequency. According to the results US/nZVI/H₂O₂ method can be good performance in removal of antibiotics Tinidazol and similar pollutants.